Evaluation of the 6‐item Identify Chronic Migraine screener in a large medical group. Issue 2 (9th January 2021) - Pavlovic, Jelena M.; Yu, Justin S.; Silberstein, Stephen D.; Reed, Michael L.; Cowan, Robert P.; Dabbous, Firas; Pulicharam, Riya; Viswanathan, Hema N.; Lipton, Richard B.
Abstract: Objective: To evaluate the sensitivity and specificity of the 6‐item Identify Chronic Migraine screener (ID‐CM[6]), designed to improve the detection of chronic migraine (CM). Background: CM is often undertreated and underdiagnosed. Survey‐based studies have found that approximately 75–80% of people meeting criteria for CM do not report having received an accurate diagnosis. Methods: This study used claims data of patients enrolled in a large medical group who had at least one medical claim with an International Classification of Diseases 9th/10th revision diagnostic code for migraine in the 12‐month prescreening period. The Identify Chronic Migraine survey was administered by e‐mail, in‐person, or over the telephone to all enrolled patients. A Semi‐Structured Diagnostic Interview (SSDI) was administered by telephone by a trained physician. The ID‐CM(6) and SSDI classifications of CM status were compared to evaluate sensitivity and specificity of the ID‐CM(6) screening tool. Results: The analysis of the ID‐CM(6) screening tool included 109 patients, with 65/109 (59.6%) positive for CM based on the SSDI. The mean (standard deviation) age of the patient sample was 49 (15) years and 100/109 (91.7%) were female. Using the SSDI as the diagnostic gold standard, the ID‐CM(6) had a sensitivity of 70.8% (46/65) and a specificity of 93.2% (41/44). Conclusion: The ID‐CM(6) demonstrated acceptable sensitivity and good specificity in determining CM status. The results of this analysis support the real‐world utility of the ID‐CM(6) as a simple and useful tool to identify patients with CM.